2016
DOI: 10.1186/s12905-016-0341-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the diagnostic value of CD138 for chronic endometritis, the risk factors for the pathogenesis of chronic endometritis and the effect of chronic endometritis on pregnancy: a cohort study

Abstract: BackgroundTo investigate the role of CD138 immunohistochemistry in the diagnosis of chronic endometritis (CE) and the risk factors for assisted conception patients having CE complications.MethodsNinety-three patients, with normal uterine shape confirmed by examination and who were planning to undergo assisted conception treatments, were selected as research subjects. Endometrial tissue was isolated for routine hematoxylin and eosin (HE) and CD138 immunohistochemical staining. Additionally, the disease historie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 12 publications
4
70
0
15
Order By: Relevance
“…Thus, it was thought to be a benign condition for which the purpose of diagnosis and treatment were not clear and would require endometrial specimens, which can burden the patient . However, recent research has suggested that CE adversely affects fertility, proposing a pathological role for CE . In the present review, the aim was to clarify the concept of CE, with a particular focus on its etiology, epidemiology, clinical features, pathophysiology, diagnosis and treatment of CE involved in reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was thought to be a benign condition for which the purpose of diagnosis and treatment were not clear and would require endometrial specimens, which can burden the patient . However, recent research has suggested that CE adversely affects fertility, proposing a pathological role for CE . In the present review, the aim was to clarify the concept of CE, with a particular focus on its etiology, epidemiology, clinical features, pathophysiology, diagnosis and treatment of CE involved in reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…fertility, proposing a pathological role for CE. [5][6][7][8] In the present review, the aim was to clarify the concept of CE, with a particular focus on its etiology, epidemiology, clinical features, pathophysiology, diagnosis and treatment of CE involved in reproduction.…”
mentioning
confidence: 99%
“…При ХЕ вірогідно знижена експресія рецепторів про-гестерону та естрадіолу, особливо ці зміни ви-ражені в стромі. З цими порушеннями пов'я-зані як недостатня товщина ендометрія, так і різні форми його гіперплазії [2,5].…”
Section: аналіз літературних даних та постановка завдання дослідженняunclassified
“…Найбільш сталою на сьогодні є точка зору про виник-нення ХЕ в результаті дисбалансу між гормональною та імунною системами організму, з одного боку, і патогена-ми, представниками мікробіоценозу -з іншого [2,4]. Ве-лика кількість повторних спроб ЕКЗ в анамнезі або гормо-нальний вплив при застосуванні комбінованих оральних контрацептивів змінюють співвідношення імунокомпе-тентних клітин ендометрія на локальному рівні, що при-зводить до переважання функції Т-хелперів 1-го типу, синтезу прозапальних цитокінів та хронізації запального процесу.…”
Section: результати дослідження та їх обговоренняunclassified
See 1 more Smart Citation